Psychological Support during Surgical Treatment of Children Ill with Respiratory Tuberculosis - O. S. Sheloumova; N. V. Zolotova (Туберкулез и болезни лёгких)
The objective: to analyze changes in psycho-emotional status of children ill with respiratory tuberculosis (RTB) in the perioperative period while the children were provided with psychological support.Subjects and Methods. 15 respiratory tuberculosis patients aged 7−12 years who received psychological support during surgical treatment were enrolled in the study. The data of psychological examination in the preoperative, early postoperative and late postoperative periods are presented.Results. In the preoperative period, the vast majority of children with respiratory tuberculosis showed a higher level of neuropsychic tension (86.7% of patients) and anxiety (73.3% of patients). When psychological support was provided during surgical treatment, the program of which was based on EMDR approach and mindfulness, in the early postoperative period, there was a significant decrease in the number of children with a high level of neuropsychic tension – from 86.7% to 46.7% (p<0. 01). At the beginning of the late postoperative period, parameters of psychoemotional status in the overwhelming majority of children were within the range of normal values.